2010
DOI: 10.1007/s10753-010-9281-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Liver X Receptor Alpha (LXRα) in Myocardium of Streptozotocin-Induced Diabetic Rats

Abstract: The present study was designed to investigate the myocardial expression of liver X receptor alpha (LXRα) in a streptozotocin (STZ)-induced diabetic rat model. Immunohistochemical staining, quantitative real-time RT-PCR, and Western blot analysis were used to determine the expression of LXRα in the myocardium of STZ-induced diabetic rats. The myocardial expression of LXRα target genes, long-chain acyl-CoA synthetase 3 (ACSL3), fatty acid transporter protein (FAT/CD36), ATP-binding cassette transporter A1 (ABCA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
1
22
1
1
Order By: Relevance
“…A rat DCM model was induced as described previously (24). In brief, 30 rats were injected intraperitoneally with 60 mg/kg body weight of STZ (Sigma) prepared in 0.1 ml citrate buffer (0.1 mmol/l, pH 4.5) to induce diabetic conditions, while 8 rats received an equal volume of vehicle and served as a non-diabetic group.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…A rat DCM model was induced as described previously (24). In brief, 30 rats were injected intraperitoneally with 60 mg/kg body weight of STZ (Sigma) prepared in 0.1 ml citrate buffer (0.1 mmol/l, pH 4.5) to induce diabetic conditions, while 8 rats received an equal volume of vehicle and served as a non-diabetic group.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (24). The hearts were lysed in radioimmunoprecipitation (RIPA) assay buffer (Beyotime Institute of Biotechnology, Haimen, China).…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…LXR expression has been identified in human and rodent cardiac tissue [2,5,6,7]. LXRβ is the dominant isoform in the heart of mice [2,5,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the results obtained by other authors. Cheng et al [9] showed that during the 20-week study, LXRα expression gradually increased in the ventricles and atria of STZ-diabetic rats. Wang et al [25] observed that 5 weeks after injection of streptozotocin mRNA expression of both LXR isoforms was markedly enhanced in the rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, synthetic LXR agonists stimulate hepatic lipogenesis by induction of expression of SREBP-1c, which results in liver steatosis and hypertriglyceridemia [6,7]. LXR expression has been identified also in the rodent cardiac tissue, and LXRβ is the dominant isoform [2,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%